Flower Color as Predictor for Nectar Reward Quantity in an Alpine Flower Community - Streinzer, Martin; Neumayer, Johann; Spaethe, Johannes (Frontiers in Ecology and Evolution, 2021)
Entomophilous plants have evolved colorful floral displays to attract flower visitors to achieve pollination. Although many insects possess innate preferences for certain colors, the underlying proximate and ultimate causes for this behavior are still not well understood. It has been hypothesized that the floral rewards, e.g. sugar content, of plants belonging to a particular color category correlate with the preference of the flower visitors. However, this hypothesis has been tested only for a subset of plant communities worldwide. Bumble bees are the most important pollinators in alpine environments and show a strong innate preference for (bee) “UV-blue” and “blue” colors. We surveyed plants visited by bumble bees in the subalpine and alpine zones (> 1400 m a.s.l.) of the Austrian Alps and measured nectar reward and spectral reflectance of the flowers. We found that the majority of the 105 plant samples visited by bumble bees fall into the color categories “blue” and “blue-green” of a bee-specific color space. Our study shows that color category is only a weak indicator for nectar reward quantity; and due to the high reward variance within and between categories, we do not consider floral color as an honest signal for bumble bees in the surveyed habitat. Nevertheless, since mean floral reward quantity differs between categories, naïve bumble bees may benefit from visiting flowers that fall into the innately preferred color category during their first foraging flights.